Limited Achievements Obama’s Foreign Policy - Laïdi, Z. (The Sciences Po Series in International Relations and Political Economy, 2012)
Through an analysis of the general principles of Obama's foreign policy, LaIdi shows how Obama has charted a realist course in the Middle East, in Europe, in diplomacy, and in war.